Errare Humanum Est (To Err Is Human): A Mentalizing Breakdown in the Therapeutic Work With an Adolescent - Wiwe, Maria (Frontiers in Psychology, 2021)
The therapeutic stance in therapies conceptualized by the two-person psychology (Wachtel, 2010) binds the therapist to genuine self-scrutiny. The concepts of transference and countertransference are viewed as jointly constructed endeavors between therapist and client, wherein the therapist needs to be aware of her contribution to difficulties arising in the therapeutic dyad. Different conceptualizations of this therapeutic technique have been eloquently described elsewhere throughout the years in terms of intersubjectivity (Stern, 2005; Aron, 2006), mentalizing (Fonagy and Bateman, 2006), mindfulness-in-action (Safran et al., 2001), rupture and repair (Newhill et al., 2003), and epistemic trust (Fonagy and Allison, 2014). These concepts will be presented interchangeably with a clinical vignette delineating a rupture in the therapeutic work with an adolescent. Finally, the article concludes with a discussion of identifying non-mentalizing modes (Allen et al., 2008) within the therapist to get back on track and restore epistemic trust (Fonagy et al., 2014) in the therapeutic relationship.